Best Decision Support System in University Lecturers Ubudiyah Indonesia Using Weighted Product (WP) - Musraidi, Desri; Muttaqin, Muttaqin (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
Besides carefulness factor, the time required to evaluate the best lecturers also influence the policy making. Especially with the large number of participants lecturers, would require a long time to make decisions and human resources needed to evaluate the best lecturers in taking decisions cepatr, precise and objective. Decision support systems research the best lecturer at the University of Indonesia Ubudiyah (UUI) is using the weighted product method. The process of the weighted product methodis to determine the weight values for each criterion, then do the process rank to select an alternative from a number of alternatives exist. The system is made in this study is a dynamic system, according to the type of existing needs. The final results of this study were able to overcome the problemsin the selection of the best professors at the University of Indonesia Ubudiyah (UUI).Keywords : Decision Supporting System, BestLecturers, University of Indonesia Ubudiyah,Weighted Produt